E. coli-Produced BMP-2 as a Chemopreventive Strategy for Colon Cancer: A Proof-of-Concept Study - Saravanan Yuvaraj; Sa’ad H. Al-Lahham; Rajesh Somasundaram; Patrick A. Figaroa; Maikel P. Peppelenbosch; Nicolaas A. Bos (Gastroenterology Research and Practice)
Colon cancer is a serious health problem, and novel preventive and therapeutical avenues are urgently called for. Delivery of proteins with anticancer activity through genetically modified bacteria provides an interesting, potentially specific, economic and effective approach here. Interestingly, bone morphogenetic protein 2 (BMP-2) is an important and powerful tumour suppressor in the colon and is thus an attractive candidate protein for delivery through genetically modified bacteria. It has not been shown, however, that BMP production in the bacterial context is effective on colon cancer cells. Here we demonstrate that transforming E. coli with a cDNA encoding an ileal-derived mature human BMP-2 induces effective apoptosis in an in vitro model system for colorectal cancer, whereas the maternal organism was not effective in this respect. Furthermore, these effects were sensitive to cotreatment with the BMP inhibitor Noggin. We propose that prevention and treatment of colorectal cancer using transgenic bacteria is feasible.